POPULATION GENETIC DIVERSITY OF CAMELLIA DILINHENSIS ON THE DI LINH PLATEAU OF VIETNAM REVEALED BY ISSR AND SCOT MARKERS - Ngoc Trieu Le; Thach Bich Thai; Van Ket Nguyen (Tạp chí Khoa học Đại học Đà Lạt)
Genetic diversity of naturally distributed Camellia dilinhensis populations on the Di Linh plateau of Vietnam was assessed by the inter-simple sequence repeat (ISSR) and start codon targeted (SCoT) techniques separately and then by combining data from both techniques for satisfactory results. The genetic diversity parameters and genetic distances among individuals found with the ISSR technique (HeI = 0.1420, II = 0.2092, PPBI = 35.22%, GSCsI = 0.765–0.988, and AGSCI = 0.915) are lower than those found with the SCoT technique (HeS = 0.2100, IS = 0.381, PPBS = 52.27%, GSCsS = 0.644–0.985, and AGSCS = 0.866). Based on the combined data from both techniques, the level of genetic diversity of the investigated population is PPB = 43.77%, He = 0.1720, I = 0.2582, and the genetic similarities among individuals are GSCs = 0.764–0.973 with an average of AGSC = 0.894. The SCoT technique differentiated between individuals better and reflected a higher level of genetic diversity in the population than the ISSR technique, but the ISSR technique revealed more loci in Camellia dilinhensis plants than did the SCoT technique.